إسهامات المراجعة الداخلية في تفعيل إدارة المخاطر - لعبيدي, د / مهاوات (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
إن حماية المؤسسة من كل المخاطر التي يمكن أن تتعرض لها ملقاة على عاتق مسؤولية الإدارة وهذا ما جعلها تبحث عن الأساليب والأنظمة التي تمكنها من تبرئة مسؤوليتها أمام مجلس الإدارة والأطراف الأخرى, ولا يتسنى لها ذلك إلا من خلال تطبيق نظام إدارة المخاطر, فهذا النظام يمكن له مساعدة المؤسسة          في اكتشاف كل المخاطر التي يمكن       أن تهددها, وإبلاغ الإدارة بذلك ومتابعة كيفية علاجها وقد تصادف المعلومات التي تبني عليها إدارة المخاطر عملها مشكلة عدم وضوحها بشكل صحيح أو معلومات صحيحة لا يمكن الاعتماد عنها بشكل كافي في عملية تحليل وتقييم المخاطر المتعلقة بها, وهذا ما يدعو إلى تفعيل نظام إدارة المخاطر من خلال المراجعة الداخلية أي المراجع الداخلي والفريق الذي يعمل معه, والذي يمكن أن يكون له الدور في مراجعة النشاط  الذي تقوم به إدارة المخاطر, والحكم عليها من خلال تقارير المراجعة الداخلية التي يقوم بإعدادها للإدارة The protection of the institution of all the risks that can be exposed to rests with the responsibility of management. This  has made the administration looking for methods and systems that enable them to acquit its responsibility in front of the Board of Directors and the other parties. It can do this only through the application of risk management system.  This system can it help the organization in the discovery of all the dangers that can threaten it  and therefore inform the administration  about that and follow up how to treat them. The information  that are built upon risk management  work may come across the problem of the lack of clarity correctly or correct information can not be relied on them adequately in the process of analyzing and evaluating risks related to it.  This leads to the activation of  the risk management system through the internal audit ,i,e the internal auditor and the team that works with them, which could have a role in reviewing the activity that is performed by the management of  risks and judge it  by the internal audit reports prepared by the administration .